Pediatric Abusive Head Trauma: A Systematic Review - Aniello Maiese; Francesca Iannaccone; Andrea Scatena; Zoe Del Fante; Antonio Oliva; Paola Frati; Vittorio Fineschi (Diagnostics, 2021)
Abusive head trauma (AHT) represents a commonly misdiagnosed condition. In fact, there is no pathognomonic sign that allows the diagnosis in children. Therefore, it is such an important medico-legal challenge to evaluate reliable diagnostic tools. The aim of this review is to evaluate the current scientific evidence to assess what the best practice is in order to diagnose AHT. We have focused particularly on evaluating the importance of circumstantial evidence, clinical history, the use of postmortem radiological examinations (such as CT and MRI), and the performance of the autopsy. After autopsy, histological examination of the eye and brain play an important role, with attention paid to correlation with symptoms found in vivo.